A comparison between thin film solar cells made from co‐evaporated CuIn1‐xGaxSe2 using a one‐stage process versus a three‐stage process. (4th January 2014) - Salomé, Pedro M.P.; Fjällström, Viktor; Szaniawski, Piotr; Leitão, Joaquim P.; Hultqvist, Adam; Fernandes, Paulo A.; Teixeira, Jennifer P.; Falcão, Bruno P.; Zimmermann, Uwe; da Cunha, António F.; Edoff, Marika
Abstract Until this day, the most efficient Cu(In, Ga)Se2 thin film solar cells have been prepared using a rather complex growth process often referred to as three‐stage or multistage. This family of processes is mainly characterized by a first step deposited with only In, Ga and Se flux to form a first layer. Cu is added in a second step until the film becomes slightly Cu‐rich, where‐after the film is converted to its final Cu‐poor composition by a third stage, again with no or very little addition of Cu. In this paper, a comparison between solar cells prepared with the three‐stage process and a one‐stage/in‐line process with the same composition, thickness, and solar cell stack is made. The one‐stage process is easier to be used in an industrial scale and do not have Cu‐rich transitions. The samples were analyzed using glow discharge optical emission spectroscopy, scanning electron microscopy, X‐ray diffraction, current–voltage‐temperature, capacitance‐voltage, external quantum efficiency, transmission/reflection, and photoluminescence. It was concluded that in spite of differences in the texturing, morphology and Ga gradient, the electrical performance of the two types of samples is quite similar as demonstrated by the similar J–V behavior, quantum spectral response, and the estimated recombination losses. Copyright © 2014 John Wiley & Sons, Ltd.